Characterization of Portuguese Thymbra capitata, Thymus caespititius and Myrtus communis essential oils in topical formulations. (5th June 2017) - Neves, A.; Marto, J.; Duarte, A.; Gonçalves, L. M.; Pinto, P.; Figueiredo, A. C.; Ribeiro, H. M.
Abstract: As the personal care industry evolves, formulators are seeking innovative solutions for their formulations' needs, and for ingredients that can offer multiple functions within formulations. Considering that essential oils (EOs) may present a wide spectrum of biological activities, the composition, antimicrobial and antioxidant activity of Portuguese Thymbra capitata, Thymus caespititius and Myrtus communis EOs were assessed in order to evaluate them as preservatives and antioxidants in topical emulsions. The in vivo safety application of some emulsions was also tested. T. capitata EO was mainly constituted by carvacrol (73%), whereas α‐terpineol (27%), p ‐cymene (14%) and carvacrol (10%) dominated Th. caespititius EO, and 1, 8‐cineole (37%) was dominant in M. communis EO. The minimum inhibitory concentration of T. capitata, Th. caespititius and M. communis EOs was 0.4 μg/mL against C. albicans and ranged between 0.4 and 30.7 μg/mL against A. brasiliensis . Gram‐positive bacteria were more susceptible to each EO than Gram‐negative bacteria. T. capitata EO showed significantly higher antioxidant activity than Th. caespititius and M. communis EOs. EOs incorporated in emulsions showed preservative activity against all microorganisms tested and T. capitata EO emulsions showed powerful reactive oxygen species (ROS) scavenging effects. A safety evaluation study was performed with 0.10% and 0.01% T. capitata EO emulsions according to the Human Repeat Insult Patch Test (HRIPT). All emulsions were considered safe for topical application. T. capitata, Th. caespititius and M. communis significantly improved the microbiological quality of the prepared emulsions and may constitute a powerful alternative to the current preservatives and antioxidants for use in topical formulations. Abstract : All emulsions were considered safe for topical application. T. capitata, Th. caespititius and M. communis significantly improved the microbiological quality of the prepared emulsions and may constitute a powerful alternative of the current preservatives and antioxidants for use in topical formulations.